Фразеологія як відбиття національної ідентичності в мас-медійних координатах - Сизонов, Д.Ю. (Мовознавство, 2019)
У статті аналізується українська фразеологія як вербалізований ідентифікатор національної культури та соціально-політичних подій в Україні. Уточнено поняття фразеостилеми (за Б. Тошовичем) та розширено функціональні межі фразеологічної картини світу / медіафразеологічної картини світу. Отримані результати сприятимуть ідентифікуванню українського масмедійного тексту зпоміж інших за допомогою фразеологічного ресурсу. The article analyzes Ukrainian phraseology in the context of broad approach adopted
in world stylistics. Phraseologisms are considered in mass consciousness as: (a) verbalized
identifiers of national culture; (b) markers of social transformations in Ukraine; (c)
conceptual ideologues of political processes. A new viewpoint on phraseology is formed in
the context of neolinguistics – a conditional combined nomination of innovative linguistics
directions with new views and ideas that are relevant today. Due to the fact that phraseology
is a complex fragment of language picture of the world, it actually expresses material and
spiritual culture of people. It is through mass communication that phraseologisms play a
leading role in identifying national and cultural features. The author expands functional
limits of phraseological picture of the world and clarifies the concept of phraseological
stylema (by B. Toshovich). Phraseostylems become especially relevant in mass media
texts if they are of a certain conceptual nature. This particularly applies to: (1) usus
phraseology; (2) transformed phraseology; (3) new phraseology. The concept of media
phraseological picture of the world is developed, which is understood as verbalization of
conceptual picture of the world that is manifested in dynamic accumulative processes of
information in mass consciousness and serves as its transponder in public communication.
The conclusions drawn will help to identify a Ukrainian media text among other media
texts through a phraseological resource. When considering a media phraseologism as
an identifier of Ukrainians, its cultural specificity is taken into account, especially when
it comes to mass communication. The author believes that in the process of scientific
interpreting of traditional phraseologisms in media or their transformed analogues national
specificity of communicators should be taken into account, which is primarily related to
the background knowledge as well as historical and cultural processes.